2004
DOI: 10.1118/1.1645680
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted 3D-TRUS guided prostate brachytherapy: System integration and validation

Abstract: Current transperineal prostate brachytherapy uses transrectal ultrasound (TRUS) guidance and a template at a fixed position to guide needles along parallel trajectories. However, pubic arch interference (PAI) with the implant path obstructs part of the prostate from being targeted by the brachytherapy needles along parallel trajectories. To solve the PAI problem, some investigators have explored other insertion trajectories than parallel, i.e., oblique. However, parallel trajectory constraints in current brach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
119
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(120 citation statements)
references
References 16 publications
1
119
0
Order By: Relevance
“…Fenster and colleagues have made major strides toward a more clinically feasible TRUSguided robotic prostate brachytherapy system (Wei et al, 2004). They adopted an industrial serial-link robot for needle manipulation while motorizing a conventional TRUS probe to produce a smooth sagittal sweep in the rectum.…”
Section: Introductionmentioning
confidence: 99%
“…Fenster and colleagues have made major strides toward a more clinically feasible TRUSguided robotic prostate brachytherapy system (Wei et al, 2004). They adopted an industrial serial-link robot for needle manipulation while motorizing a conventional TRUS probe to produce a smooth sagittal sweep in the rectum.…”
Section: Introductionmentioning
confidence: 99%
“…With this mode of therapy, a high radiation dose can be delivered locally to the tumor with rapid dose falloff in the surrounding normal tissue. Recently, several research groups have reported the investigation and development of the robotic systems for the prostate seeds implants, (Stoianovici et al, 2003), (Wei et al, 2004), (Fichtinger et al, 2006), , (Meltsner, 2007), , (Stoianovici et al, 2007), , (Salcudean et al, 2008), (Lin et al, 2008), (Moerland et al, 2008). The potential advantages of the robotic seed implants include improving the accuracy of the needle placement and seed delivery, as well as improving the consistency of the seed implant.…”
Section: Brachytherapy Roboticsmentioning
confidence: 99%
“…In brachytherapy, the radioactive sources are guided into or near the tumour through needles. A number of groups are currently working on prototypes and have demonstrated the feasibility of using robots as a moveable needle guide (Dimaio et al, 2007;Wei et al, 2004) leaving the actual insertion of the needle into the target organ to the physician. Other groups are working on placing radioactive seeds directly into the lesion, e.g.…”
Section: Literature On Robots In Radiotherapymentioning
confidence: 99%